Manajemen Pembangunan Twin Road Maospati-Sukomoro Dalam Penyediaan Infrastruktur Jalan Di Kabupaten Magetan - Wendhartama, Rizal Aziz (Jurnal Administrasi Publik, 2014)
Abstract: The Management of Maospati-Sukomoro Twin Road Development to Provide Road Infrastructure in Magetan Regency. A road development Twin Road is considered as a method to facilitate the traffic access from Magetan to Madiun. The development starts in 2010 but on September 18 of 2012, The Official of Public Works of East Java Province has decided to stop Twin Road development. A related reason why this 79.5 billions project is stopped because it is disapproved by the regulation. Research method is descriptive analysis with qualitative approach. The analysis model is Miles and Huberman’s qualitative study. Result of research has shown that the management of Maospati-Sukomoro Twin Road Development has involved planning, budgeting, human resource empowerment, the relationship between government and community, and monitoring and control. All these activities are in good condition. However, the governments of the Regency and the Province are lacking of coordination in administering the permission. Other constraining factors are problems related to land clearance and limited budget. Keywords: Management of Development, Infrastructure, Magetan Regency. Abstrak: Manajemen Pembangunan Twin Road Maospati-Sukomoro Dalam Penyediaan Infrastruktur Jalan Di Kabupaten Magetan. Pembangunan Twin Road (Jalan Kembar) merupakan salah satu cara untuk memperlancar akses lalu lintas Magetan menuju Madiun. Pembangunan dimulai tahun 2010 tetapi pada tanggal 18 September 2012 Dinas PU Provinsi Jawa Timur menyatakan pembangunan Twin Road tersebut dihentikan. Penyebab proyek senilai 79,5 Miliar ini dihentikan karena menyalahi aturan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dan analisis data Miles Huberman. Hasil penelitian ini menunjukkan dalam manajemen pembangunan Twin Road Maospati-Sukomoro yang meliputi perencanaan, penganggaran, pemberdayaan SDM, hubungan pemerintah dengan masyarakat maupun pengawasan dan pengendalian berjalan dengan baik. Tetapi dalam koordinasi pemerintah kabupaten terkait perizinan dengan Pemerintah provinsi belum berjalan dengan baik. Sedangkan kendala yang dihadapi adalah masalah pembebasan lahan dan keterbatasan anggaran. Kata Kunci: Manajemen Pembangunan, Infrastruktur, Kabupaten Magetan.